Anatomical Characters of Shoot Apical Meristem (SAM) on Bulbil Porang (Amorphophallus muelleri Blume) At the End of Dormancy Period - Afifi, Muhammad Naufal; Harijati, Nunung; Mastuti, Retno (Graduate School, Universitas Brawijaya, 2019)
Porang is one species member of the genus Amorphophallus. In Indonesia, Porang is cultivated extensively because it has a high economic value. There is three seeded material available for planting. One of seeded material is bulbil. Bulbil is a vegetative reproductive organ of Porang plants which is located in the branch of the leaf. Bulbil has 3 - 4 months dormancy period. The dormancy period will end with shoot growth. Morphologically, there can be found a rough structure in the form of bulges in bulbil. The bulge is spread throughout the bulbil surface and is a growing area of shoots. Shoots on bulbil will grow through the bulge and only grow on the adaxial part, contrary shoots do not grow from the abaxial part. This study aims to compare the anatomy of shoot apical meristem (SAM) in the adaxial and abaxial parts of bulbil at the end of the dormancy period, ie 100 days after harvest (DAH), 110 DAH, 120 DAH, and 130 DAH. Anatomical observations were carried out by making semi-permanent preparations. The results showed that the anatomy of the adaxial and abaxial parts of bulbil Porang had differences in the development of SAM, leaf primordia, primary thickening meristem (PTM) and procambium.Keywords: Anatomy, Bulbil Porang, Dormancy, Shoot Apical Meristem.